KEBIJAKAN HUTANG, TATA KELOLA PERUSAHAAN DAN MANAJEMEN LABA AKRUAL - Yudy, Yudy; Susanto, Yulius Kurnia (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2018)
The purpose of the study was to obtain empirical evidence about the effect of debt policy, director size, director independence, institutional ownership, and female directors on accrual earnings management. Samples were obtained through purposive sampling method as many as 102 manufacturing companies listed on the Indonesia Stock Exchange from 2013 to 2016. The results showed that debt policy had a significant effect on accrual earnings management. While the director's size, director's independence, institutional ownership, and female directors do not have a significant effect on accrual earnings management. Management does not dare to make accrual earnings management because they get close supervision from creditors.